2008
DOI: 10.1007/s11255-008-9479-8
|View full text |Cite
|
Sign up to set email alerts
|

Male–female differences in the risk of tuberculosis in dialysis patients

Abstract: In contrast to the general population, there is a female predominance among dialysis TB patients younger than 70 years associated with the coexistence of DM. Female gender should always be considered as a risk factor when evaluating diabetic HD patients for active TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…A higher indeterminate QFT rate in female patients was reported in one study, although the reason for these findings was not elucidated [19]. One report showed a female predominance among dialysis TB patients despite a higher frequency of male than female patients reported with TB in general [24]. However, no gender differences in QFT results were found in our study.…”
Section: Discussioncontrasting
confidence: 76%
“…A higher indeterminate QFT rate in female patients was reported in one study, although the reason for these findings was not elucidated [19]. One report showed a female predominance among dialysis TB patients despite a higher frequency of male than female patients reported with TB in general [24]. However, no gender differences in QFT results were found in our study.…”
Section: Discussioncontrasting
confidence: 76%
“…This ratio in hemodialysis patients is reduced to 1.1. [25] In In an another study,[26] out of 272 hemodialysis patients, female patients had presented significantly lower cell mediated immunity indices and rates of positive TSTs, but, higher rates of diabetes mellitus as compared to males. The male: female ratio in tuberculosis for the general and hemodialysis patient population was 2.4 and 0.6 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…11.3%). [26] When we reviewed our data, it was found that the all miners were males. All the patients who had a past history of tuberculosis were also males.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of tuberculosis in this population is frequently difficult and delayed because of the high frequency of extrapulmonary involvement and nonspecific symptoms [2][3][4][5][6]. Currently, it is recommended that all patients with end-stage kidney disease should be screened for latent tuberculosis infection with PPD (tuberculin) skin testing [7].…”
Section: Discussionmentioning
confidence: 99%